Regime hídrico de alguns solos de Jaboticabal - Centurion, J. F. [UNESP]; Andrioli, I. [UNESP] (Sociedade Brasileira de Ciência do Solo, 2000)
The hydric characterization of the soils of the Campus of the Faculdade de Ciências Agrárias e Veterinárias in Jaboticabal, SP, Brazil has certified that the Red Latosol presented the largest available soil water capacity and that the amount of water held at field capacity (0.01 MPa) and permanent wilting point (1.5 MPa) was better correlated to the clay and silt contents, as compared to the organic matter content and soil bulk density. Using the hydric characteristics of the soils, their moisture regime was established, by means of the Thornthwaite water balance. It was verified that for all soils (Eutrustox and Kandiustalf) the ustic soil moisture regime prevailed.

Na caracterização hídrica dos solos do Campus da Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal (SP), verificou-se que o Latossolo Vermelho eutroférrico típico apresentou maior capacidade de água disponível. A retenção da água, na capacidade de campo (0,01 MPa) e ponto de murcha permanente (1,5 MPa), correlacionou-se melhor com as frações argila e silte, em relação ao teor de matéria orgânica e densidade do solo. Utilizando características hídricas, como a capacidade de água disponível, foi estabelecido por meio do balanço hídrico de Thornthwaite o regime hídrico para os solos. Verificou-se a predominância do regime hídrico ústico em todos os solos (Latossolo Vermelho Nitossolo).
Hydric regime of some soils of Jaboticabal
Keywords: capacidade de água disponível; classificação do solo; propriedades físico-hídricas; available soil water; soil classification; physical and hidraulic properties